Expression Changes of the FOXE1 and lncRNA PTCSC2 Expression in Tumor Tissues Compared with Normal Tissues in Patients with Colorectal Cancer - Marzieh Ghani Dehkordi; Maryam Peymani (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2022)
Introduction: In recent studies, methylation of FOXE1 in colorectal cancer has been reported as a diagnostic biomarker. In this study for the first time, the expression of FOXE1 and PTCSC2 in colorectal cancer was investigated and their expression patterns in two healthy and tumor tissues of patients were compared. Methods: In this study, 40 tumor tissues with colorectal cancer and 40 adjacent normal samples were collected. Total RNA was extracted and cDNA synthesis followed. Then, the specific genes for lncRNA PTCSC2 and FOXE1 were amplified. The results were statistically analyzed by Graph Pad Prism software and a T-test was used to compare the expression levels of lncRNA PTCSC2 and FOXE1 in the patients and healthy group; p-value less than 0.05 was considered significant difference criteria. Results: In this study, the FOXE1 expression level was significantly decreased in tumor tissue (p-value = 0.005), whereas the lncRNA PTCSC2 expression level in tumor tissue was not significantly changed (p-value = 0.65). In addition, the expression levels of FOXE1 and lncRNA PTCSC2 did not show a significant relation with disease progression and age of the patients. ROC curve for changes in FOXE1 and lncRNA PTCSC2 expression showed that theFOXE1 gene could be a relatively appropriate independent variable (p-value = 0.03) to differentiate between the two study groups. Conclusion: According to the results of this study, changes in FOXE1 gene expression were significantly reduced in tumor samples and can be used as a biomarker in tumor diagnosis in colorectal cancer.